Silicon Phthalocyanines in Large Area, Flexible Organic Photovoltaics Processed by Blade Coating - Sundaresan, Chithiravel (Université d'Ottawa / University of Ottawa, 2023)
Organic photovoltaics (OPVs) is an emerging energy technology that can offer lightweight and conformable power sources suitable for many niche applications. Currently, the most promising OPV devices are based on materials with high synthetic complexity, and they are fabricated on a lab scale via spin coating on glass substrates, with small active areas (< 0.1 cm2). While spin coating is a powerful method for uniform and controlled film deposition, it is not suited for large-scale manufacturing. In order to facilitate the transfer from laboratory to industrial production, we must use scalable deposition techniques and investigate the impact of the scalability on the properties of the active layers and the devices’ performance. Silicon Phthalocyanines (SiPcs) are a class of semiconductor molecules with low synthetic complexity that are widely used in organic electronics such as organic thin film transistors and organic light-emitting diodes. In OPVs, SiPcs were demonstrated as an effective ternary additive in spin-coated devices. However, its potential use in scalable large-area devices has not been explored yet. In this thesis, a series of SiPcs were investigated as active materials in flexible inverted OPVs, using a scalable deposition technique: the blade coating. We first used SiPcs as a ternary additive in PCDTBT: PC71BM-based bulk heterojunction (BHJ) OPVs. We demonstrated that SiPcs can effectively enhance the device’s performance by increasing the charge generation in the NIR region and maintaining an optimal nanomorphology of active layers. We achieved a maximum power conversion efficiency (PCE) of 5.5% by adding 10wt.% of SiPc. We also used SiPc as a non-fullerene acceptor, paired with P3HT polymer in an active layer processed from green solvents. The use of green processes in OPV device fabrication is crucial for the commercial deployment of the technology. We explored different active layer configurations: BHJ, sequential, and alternate-sequential (Alt-Sq). The Alt-Sq configuration, where the acceptor is deposited sequentially on top of the polymer, led to the best device performance, balanced charge carrier mobilities, and favorable morphology. The results presented in this thesis demonstrate significant steps toward large-scale implementation of SiPcs in low-cost, large-area, flexible OPVs.
Keywords: Silicon Phthalocyanines; Organic photovoltaics; Blade coating; Large-Area, Flexible